ANALISIS DAYA TAHAN PADA ATLET PENCAK SILAT ELANG KESATRIA INDONESIA DI DESA KUALU KABUPATEN KAMPAR - Sapriandi, Sapriandi; Sulastio, Agus; Rusmanto, Rusmanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to determine "Analysis of Endurance inIndonesian Eagle Knight athletes in Kualu Village, Kampar Regency". This research isclassified as a descriptive research type. The location of this research was carried outin the field of State Junior High School 3 Tambang, Kualu Village, Tambang District,Kampar Regency. The results of the research showed that the vo2max endurance levelof Indonesian Eagle Knight pencak silat athletes in Kualu village, Kampar district,showed the moderate category. The level of endurance/bleeb test in pencal silat athletesmust have good endurance. Good endurance is needed in a pencak silat competition inorder to be able to compete in three rounds. During that time, athletes must be able tocompete well in displaying their technical and tactical abilities. Athletes who have agood level of endurance will be able to do it well. On the other hand, athletes who donot have good endurance will not be able to optimally display their technical andtactical abilities.Keywords: Endurance Analysis, Pencak Silat Athletes